Concise Afrikaans-Dutch dictionary with English equivalents Abbreviations - Teurlinckx, Albert Alfred Frans (Werkwinkel, 2020)
Concise Afrikaans-Dutch dictionary with English equivalents by A.A.F. TEURLINCKX. Jac Conradie en Johanna Teurlinckx-Messerschmidt(redacteurs/redakteurs/editors).